Perception of Childhood Febrile Illness among Parents and Health Professionals: Where do We Stand? - Nazme, Nure Ishrat; Haque, Md Aynul (Jalalabad Medical Journal, 2025)
Fever is a common symptom in children, which represents one of the burning issues for parents due to excessive concern and frequent medical attention. Most febrile episodes are not harmful but could be viewed as a beneficial response to infection. Despite this, ‘’fever phobia” remains prevalent among parents, and improper handling of childhood fever has been recorded for nearly two decades. Nevertheless, numerous health professionals have documented unanticipated concerns regarding the handling of negative attitudes. This was a systematic review of the literature to explore the perception of childhood febrile illness among parents and health professionals based on a comprehensive literature search. Childhood febrile illness continues to provoke fear in both parents and healthcare providers. Healthcare professionals play a crucial role as the main source of information for parents and carry the responsibility of alleviating parental anxiety. A multicomponent intervention including training of healthcare professionals should be implemented to achieve a reduction in hospital burden and undue parental concern, thereby improving the management strategy of uncomplicated febrile illness in children. The concerning misperception regarding fever and its management in children persists among both parents and health professionals within the community, despite advancements in education and scientific knowledge. There is an utmost requirement to prepare specific guidelines and spread awareness in the community about the management of febrile illnesses in children. Jalalabad Med J 2024; 21 (2); 79-87